2017
DOI: 10.1038/s41598-017-06341-6
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence linking microRNA suppression of essential prosurvival genes with hippocampal cell death after traumatic brain injury

Abstract: The underlying molecular mechanisms of how dysregulated microRNAs (miRNAs) cause neurodegeneration after traumatic brain injury (TBI) remain elusive. Here we analyzed the biological roles of approximately 600 genes - we previously found these dysregulated in dying and surviving rat hippocampal neurons - that are targeted by ten TBI-altered miRNAs. Bioinformatic analysis suggests that neurodegeneration results from a global miRNA-mediated suppression of genes essential for maintaining proteostasis; many are hub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
(57 reference statements)
3
24
0
Order By: Relevance
“…In the brain, altered miRNA expression is linked to neurodegenerative disorders 5 . In previous rat TBI studies, we reported that 24 h after experimental TBI, injury-induced miRNAs suppressed expression of pro-survival genes in dying hippocampal neurons 6 . These miRNA target genes, according to the Online Mendelian Inheritance in Man (OMIM) database, lead to human disease when dysregulated, mutated or deleted 7 .…”
Section: High-throughput Sequencing Technologies Could Improve Diagnomentioning
confidence: 89%
“…In the brain, altered miRNA expression is linked to neurodegenerative disorders 5 . In previous rat TBI studies, we reported that 24 h after experimental TBI, injury-induced miRNAs suppressed expression of pro-survival genes in dying hippocampal neurons 6 . These miRNA target genes, according to the Online Mendelian Inheritance in Man (OMIM) database, lead to human disease when dysregulated, mutated or deleted 7 .…”
Section: High-throughput Sequencing Technologies Could Improve Diagnomentioning
confidence: 89%
“…By performing a motifs search on all DMRs, we identified 14 TF motifs ( Table 1) that were significantly enriched in agerelated DMRs in both the blood and brain suggesting potential translational relevance of the findings from this study. Six of those 14 common motifs (ELK1, ELF1, ETV1, ETV4, ETV5, RXR) have been associated with modulating synaptic density, arborization, and neurite outgrowth (Gao et al, 1996;Abe et al, 2011;Szatmari et al, 2013;Boone et al, 2017). Furthermore, ETV1, ELK1, EAR2, RXR, and GABPA have been implicated in regulating cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that MSCs promised to be an effective therapy for brain injury in TBI [175-177, 215, 231-236]. Instead of brain remodeling and functional recovery by cell replacement effects, evidence suggests that the major effects of neurorestoration were due to the paracrine effects of secretion-based factors such as MSCs-derived exosomes that may reduce neuroinflammation, promote neurogenesis and angiogenesis, rescue pattern separation and spatial learning impairments, and improve functional recovery after TBI in animal models [107,176,178,191,204,205,215,216,[235][236][237]. In addition, as exosomes contain various miRNAs, which play a key role in modifying the phenotype and/or the physiology and modulating the cellular processes of the recipient cell, and miRNAs such as miR-21 could be potential therapeutic targets for interventions after TBI, the combination of miRNAs and MSC-derived exosomes might be a novel approach for the treatment of TBI [238].…”
Section: Extracellular Vesicles and Exosomesmentioning
confidence: 99%
“…MSCs have shown promise in the field of regenerative medicine, since exogenously administered MSCs target injured tissue, interact with brain parenchymal cells, and promote neurorestoration and recovery of neurological function after brain injuries [178,191,204,205]. Despite the differentiation capacity of MSCs, the principal mechanism of their therapeutic action seems to be a robust paracrine capacity, related to their soluble factors as well as generation and release of microvesicles and exosomes [178,205].…”
Section: Extracellular Vesicles and Exosomesmentioning
confidence: 99%
See 1 more Smart Citation